The knowledge, ability, and skills of primary health care providers in SEANERN countries: a multi-national cross-sectional study - Du, Shizheng; Cao, Yuling; Zhou, Tong; Setiawan, Agus; Myat, Thandar; Koy, Virya; Nurumal, Mohd. Said; Hong, Anh; Hu, Yan (BioMed Central Ltd., 2019)
Background: Primary health care (PHC) is usually the initial point of contact for individuals seeking to access health care and providers of PHC play a crucial role in the healthcare model. However, few studies have assessed the knowledge, ability, and skills (capacity) of PHC providers in delivering care. This study aimed to identify the capacity of PHC providers in countries of the Southeast and East Asian Nursing Education and Research Network (SEANERN). Methods: A multi-national cross-sectional survey was performed among SEANERN countries. A 1–5 Likert scale was used to measure eight components of knowledge, ability, and skill of PHC providers. Descriptive statistics were employed, and radar charts were used to depict the levels of the three dimensions (knowledge, skill and ability) and eight components. Results: Totally, 606 valid questionnaires from PHC providers were returned from seven countries of SEANERN (China, Myanmar, Indonesia, Thailand, Vietnam, Cambodia, and Malaysia), with a responsive rate of 97.6% (606/621). For the three dimensions the ranges of total mean scores were distributed as follows: knowledge dimension: 2.78~3.11; skill dimension: 2.66~3.16; ability dimension: 2.67~3.06. Furthermore, radar charts revealed that the transition of PHC provider’s knowledge into skill and from skill into ability decreased gradually. Their competencies in four areas, including safe water and sanitation, nutritional promotion, endemic diseases prevention, and essential provision of drugs, were especially low. Conclusions: The general capacity perceived by PHC providers themselves seems relatively low and imbalanced. To address the problem, SEANERN, through the collaboration of the members, can facilitate the appropriate education and training of PHC providers by developing feasible, practical and culturally appropriate training plans.